PROTECTION OF CHILD REFUGEES UNDER INTERNATIONAL LAW - Sri Muliana Azhari; M. Ya’kub Aiyub Kadir (Universitas Syiah Kuala, 2021)
International law has a vital role in securing more excellent protection for refugee children. There are 82.4 million people fleeing war, violence, persecution, and human rights violations in 2020 globally, 42% of refugees are children under the age of 18. Therefore this study raised the question of what international conventions govern child refugees. This research uses normative research.The results found that the 1951 refugee convention and the 1967 protocol are international arrangements regulating refugee children. Simultaneously, the Convention on the right of Children (CRC) also offers more detailed and comprehensive legal guidelines on child care, including refugee children. Those two conventions have contributed to firm legal protection for child refugees, but there is also a weakness when a country only ratifies one of them. Thus, for legal certainty, a new legal instrument in the form of a convention on the rights of child refugees is needed to fulfill the rights of child refugees properly. Keywords: International protection, International refugee law, Child refugee.